The Holocaust, Canadian Jews, and Canada’s “Good War” Against Nazism - Erwin, Norman (Canadian Jewish Studies / Études juives canadiennes, 2016)
This paper examines the Canadian Jewish response to the Holocaust during the Second World War. Rather than disparaging the Canadian Jewish community for timidity in its dealings with Canadian institutions or suggesting that Canadian Jews were disinterested in their European brethren, historians need to contextualize Canadian Jewish actions within the domestic power structures of the 1940s and the confines of the Canadian Jewish imagination. With the Canadian Government censoring the Holocaust, the Canadian Jewish community framed the European Jewish tragedy around the idea of resistance to bolster Canadian sympathy for European Jews and give meaning to the Holocaust.